PENGARUH OTHER COMPREHENSIVE INCOME DAN NET INCOME TERHADAP RETURN SAHAM PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Dina Khairuna Siregar; Ina Khodijah (Jurnal Bina Bangsa Ekonomika, 2022)
This study is a quantitative study that aims to determine the effect of Other Comprehensive Income and Net Income on the Return on Shares of LQ45 companies listed on the Indonesia Stock Exchange in 2016-2022. The sampling technique is to use the purposive sampling method and obtained 8 companies that are research samples The data processing technique uses multiple linear regression analysis with the help of SPSS version 25. The results of this study show that Other Comprehensive Income partially has no influence on stock returns and Net Income partially has a negative influence on stock returns. Simultaneously Other Comprehensive Income and Net Income have an influence on stock returns